Self-assembled nanoparticles in ocular delivery: a comprehensive review - Shanmugam Saraswathi Tenpattinam; Sarad Pawar Naik Bukke; Praveen Kumar Kusuma; Hope Onohuean; Mohan Mothilal; Umasankar Krishnamaraju; Narayana Goruntla; Tadele Mekuriya Yadesa (Discover Applied Sciences)
Abstract Ocular nanoparticles are tiny particles designed to deliver drugs to the eye and have increased drug stability, prolonged drug release, and thereby enhanced bioavailability. Nanoparticles utilized in ocular drug delivery include liposomes, polymeric nanoparticles, solid lipid nanoparticles, nanostructured lipid carriers, dendrimers, and niosomes. Niosomes are non-ionic surfactant-based vesicles that can encapsulate both hydrophilic and lipophilic drugs and are similar to liposomes but are more stable, less toxic, and easier to produce. Niosomes can also be surface-modified with ligands (e.g., antibodies, peptides) to target specific ocular tissues or cells and hence can improve drug penetration through the corneal and conjunctival barriers. Niosomes can bind to the mucin layer of the eye, increasing medication retention time. The encapsulated medicine is released under regulated conditions, allowing therapeutic doses to be maintained for an extended time period. The present study examines niosome-based drug delivery substitutes in ophthalmology, as well as the optimization of nanocarriers for practical use in treating ocular diseases.